2020
DOI: 10.19045/bspab.2020.90154
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eggshell powder fortification on the physicochemical and organoleptic characteristics of muffins

Abstract: The present study was designed to overcome the deficiency of calcium by preparation of muffins with eggshell powder. By dietary invention such as food fortification calcium deficiency can be reduced. Bakery products are best source for fortification of food. The eggshell powder was added for fortification of muffins at 8 and 16 g/500 g flour basis, synthetic source of calcium carbonate was also added in muffins at the same level. Minerals estimation indicated increasing trend of most of the minerals. Proximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 5 publications
1
10
0
3
Order By: Relevance
“…A significant increase was also found in ash content after eggshell powder addition, which means that the mineral content was increased [ 61 ], which was in agreement with the significant increase of calcium content ( p < 0.05) ( Table 2 ). A similar increasing ash and calcium content trend was also found in biscuits [ 5 ], wheat bread [ 60 ], and muffin [ 63 ] fortified with eggshell powder. Therefore, the addition of chicken eggshell calcium into gingerbread could be an alternative to improve the calcium intake of the consumer.…”
Section: Resultssupporting
confidence: 69%
“…A significant increase was also found in ash content after eggshell powder addition, which means that the mineral content was increased [ 61 ], which was in agreement with the significant increase of calcium content ( p < 0.05) ( Table 2 ). A similar increasing ash and calcium content trend was also found in biscuits [ 5 ], wheat bread [ 60 ], and muffin [ 63 ] fortified with eggshell powder. Therefore, the addition of chicken eggshell calcium into gingerbread could be an alternative to improve the calcium intake of the consumer.…”
Section: Resultssupporting
confidence: 69%
“…The results fluctuated around 13.4 %. Afzal et al (2020) have reported that the fat content of eggshell fortified muffins decreased as the amount of added eggshell powder increased. However, in this study, slight differences in the fat content of ESP and OSP fortified biscuit samples were observed when compared to control sample.…”
Section: Chemical Composition Of Biscuitsmentioning
confidence: 99%
“…Since eggshells are good source of calcium (Naves et al, 2007), eggshell fortified foods exhibited a significant increase in calcium concentration (Afzal et al, 2020). As can be observed from Table 3, the control biscuit samples (CS) had significant amount of minerals which were possibly sourced from whole wheat flour and pounded oats.…”
Section: Minerals Compositionmentioning
confidence: 99%
See 2 more Smart Citations